Quality and storage time of traditional dangke cheese inoculated with indigenous lactic acid bacteria isolated from Enrekang District, South Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zakariah MA, Malaka R, Laga A, Ako A, Zakariah M, Mauliah FU. 2022. Quality and storage time of traditional dangke cheese inoculated with indigenous lactic acid bacteria isolated from Enrekang District, South Sulawesi, Indonesia. Biodiversitas 23: 3270-3276. Dangke is a traditional cheese from Enrekang District. Many research on the isolation of lactic acid bacteria (LAB) from dangke has been done without knowing the type of LAB species. This study aimed to find out the type of LAB species that have been successfully isolated and applied to dangke again. The design of this study was conducted in two stages: 1) isolated LAB species were identified by 16S rRNA sequencing; 2) effect of inoculated LAB on the quality and storage time of traditional dangke cheese. The molecular results showed that LAB from dangke included Streptococcus lutetiensis, Weissella confusa and Streptococcus equinus. Isolates type and ripening time have affected pH, organic matter, and dangke crude fat. The type of isolate can partially affect the dry matter content, and dangke crude protein. Weissella confusa can improve the quality of dangke with a ripening time of 6 days and a storage time of 3 days.
Keywords: Cheese, dangke, LAB species, Streptococcus equinus, Streptococcus lutetiensis, Weissella confusa